Abstract ID: 47 Modelling of a novel X-ray source for MR-guided radiotherapy. (October 2017) - Roberts, Natalia; Oborn, Brad; Begg, Jarrad; George, Armia; Alnaghy, Sarah; Causer, Trent; Alharthi, Thahabah; Jelen, Urszula; Dong, Bin; Holloway, Lois; Metcalfe, Peter
Abstract : The purpose of this work was to model a novel X-ray source that is the current linear accelerator in use for the Australian MRI-linac system. MR-guided radiotherapy is an advanced technique which combines the excellent soft tissue contrast and high temporal resolution of MR imaging with the therapeutic benefits of radiotherapy. This system will achieve real-time tumor tracking, where the treatment beam can be adapted to shifts in the tumor geometry enabling tighter dose margins with a subsequent reduction in dose to healthy tissue surrounding the target. However, the transport of radiation is influenced by the strong magnetic fields produced by the MRI-scanner and needs to be accounted for in dosimetric calculations. The experimental setup for commissioning of the system at zero field (0T) was modelled with the Monte Carlo toolkit Geant4. This configuration includes the linac, multileaf collimators (MLCs) and the phantoms used during the measurements. The simulations were two stages: an electron beam hitting the target and scoring all particles in a phasespace that cross a plane before the MLCS, in the second stage the particles pass through the MLCs and dose deposited inside the phantoms is stored. Simulations were run for open fields and MLC defined field sizes, profiles at various depths were acquired as well as percentage depth dose (PDD) curves. These results were then compared to measurements taken with a CC13 ion chamber in a water tank and Gafchromic film in solid water. To date the simulated results are in good agreement with the measured data, for open field data agreement between PDDs was within 2%. The nominal energy of the system has been determined to be within the range of 5.6–6 MV, which matches the specifications of the linac. Analysis of the energy spectrum showed the photons downstream of the linac contained a higher low energy component compared with typical clinical radiotherapy beams due to the absence of a flattening filter. This phase of the project is essential to obtain a comprehensive model of the complete system which will be used to develop a Monte Carlo treatment plan verification tool for the Australian MRI-linac.